Brain-Derived Neurotrophic Factor Val66Met Gene Polymorphism Impacts on Migraine Susceptibility: A Meta-analysis of Case–Control Studies - Terrazzino, Salvatore; Cargnin, Sarah; Viana, Michele; Sances, Grazia; Tassorelli, Cristina (Frontiers in Neurology, 2017)
Inconclusive results have been reported in studies investigating the association between the BDNF rs6265 polymorphism and migraine. In the present study, we conducted a systematic review and meta-analysis on the published data in order to quantitatively estimate the relationship between rs6265 and migraine susceptibility. A comprehensive search was performed through PubMed, Web of Knowledge and Cochrane databases up to October 2016. The pooled odds ratio (OR) with the corresponding 95% confidence interval (CI) was calculated to estimate the strength of the association with rs6265 under an additive, dominant, or recessive model of inheritance. A total of five studies including 1442 cases and 1880 controls were identified for the meta-analysis. The pooled data showed an increased risk of migraine for the allelic (OR: 1.17, 95%CI: 1.03-1.34, p=0.014) or the dominant model of rs6265 (OR: 1.22, 95%CI: 1.05-1.41, p=0.011). Statistical significance of rs6265 was lost when one single study was excluded from the analysis (dominant OR: 1.17, 95%CI: 1.00-1.38, p=0.054; allelic OR: 1.14, 95%CI: 0.99-1.31, p=0.067), suggesting lack of robustness of pooled estimates. When stratified by migraine type, a similar trend of association was detected with both MA and MO, but a statistically significant association of rs6265 was reached only with the MA subtype in the dominant model (OR: 1.22, 95%CI: 1.00-1.47, p=0.047). The present meta-analysis supports that BDNF rs6265 may act as a genetic susceptibility factor for migraine. Nevertheless, large-scale studies are required to confirm our findings and to assess potential modifiers of the relationship between rs6265 and migraine.